Recurrent bacterial vaginosis: possible ways of correction - N.F. Zakharenko; I.P. Manoliak (Publishing House TRILIST, 2021)
Research objective: to increase the effectiveness of bacterial vaginosis (BV) treatment in women of reproductive age. Materials and methods. The study involved 64 women of reproductive age with BV. After a course of local antibiotic therapy participants were divided into 2 groups: patients of group I were not prescribed local remedies to restore the vaginal microflora, patients of group II were prescribed vaginal prebiotic suppositories Folial № 10. No additional drugs were used in subgroups IA and IIA, while oral probiotic Maxibalance was prescribed in subgroups IB and IIB. The effectiveness of BV treatment was evaluated at the first, third and sixth months of the observation period according to the results of clinical examination and vaginal pH evaluation by litmus strips. Results. The course of BV in subgroup IA was characterized by prevailing number of relapses and their early appearance. 1 case of BV recurrence was found among patients of subgroup IA at the 1st month of follow-up, 6 and 8 BV episodes were found at 3 and 6 months of follow-up respectively. Sequential treatment with antibiotics and oral probiotics (subgroup IIB) was associated with the onset of 3 BV relapses on 4-5 months from baseline. Local prebiotic (subgroup IIA) after the vaginal sanation was associated with BV reoccurrence in only one patient at the end of the study. No relapses of BV were detected in subgroup IIB during the study. Conclusions. Permanent imbalance of vaginal normocenosis creates optimal conditions for chronic and recurrent diseases of dysbiosis nature, especially BV. Despite the sensitivity of the anaerobic flora to the recommended antibacterial medications, their use as monotherapy in BV treatment is often insufficient. The results of the study demonstrate a significant anti-relapse efficiency of consecutive treatment by antibacterial drugs and a complex of probiotic + prebiotic. This effect is probably based on the restoration of vaginal immunity and metabolism by stable colonization of the vaginal mucosa with live lactobacilli of eubiotic origin.